Development of Immature CD4+CD8+T Cells Into Mature CD4+ T Cells Requires Alpha-1 Antitrypsin as Observed by Treatment in HIV-1 Infected and Uninfected Controls - Bristow, Cynthia L.; Ferrando-Martinez, Sara; Ruiz-Mateos, Ezequiel; Leal, Manuel; Winston, Ronald (Frontiers in Cell and Developmental Biology, 2019)
Immune cells are, by default, migratory cells that traverse tissue for the purpose of carrying out recognition and recruitment in pathologic inflammation and infection. Members of the LDL receptor family (LDL-RFMs) interact with human leukocyte elastase on the cell surface (HLE-CS) in complex with the abundant blood protein α1proteinase inhibitor (α1PI, α1-antitrypsin, Alpha-1), a process that induces internalization of aggregated functionally-related receptors, including CD4 and the T cell antigen receptor, while simultaneously promoting cellular locomotion. We sought to determine whether augmenting α1PI blood concentration would promote the locomotion of immature T cells through the thymus and generate new CD4+ T cells. Two small clinical trials (NCT01370018, NCT01731691, https://clinicaltrials.gov) were conducted in which HIV-1 infected and uninfected individuals were augmented with α1PI and compared with placebo-treated subjects and untreated controls. Blood cell phenotypes were monitored weekly. We found that CD4/CD8 ratio was significantly increased by α1PI augmentation in both uninfected and HIV-1 infected individuals. We found that maturation of CD4+CD8+ T cells to become immunologically competent CD4+ T cells was regulated by α1PI. We propose a strategy targeting HLE-CS for treating secondary immunodeficiency for which there is currently no direct treatment. Treatment to directly elevate T cells in patients with secondary immunodeficiency, including HIV disease, can be provided by alpha-1 antitrypsin augmentation or small molecules that target HLE-CS. Because individuals infected with HIV-1 produce a monoclonal antibody, 3F5, which binds to and inactivates α1PI, a process that prevents α1PI from binding to HLE-CS, thereby blocking locomotion of immature T cells through the thymus to generate CD4+ T cells, we further propose that HIV-1 vaccination should include induction of an antibody that binds to and blocks 3F5 activity, thereby preventing AIDS in addition to the current vaccine strategy for preventing HIV-1 infection.